Racial Disparities in Medication Adherence Barriers: Pediatric Epilepsy as an Exemplar. (12th January 2022) - Gutierrez-Colina, Ana M; Wetter, Sara E; Mara, Constance A; Guilfoyle, Shanna; Modi, Avani C
Abstract: Objective: To evaluate how racial disparities in medication adherence barriers relate to key clinical outcomes (i.e., seizure control and adherence) in pediatric epilepsy and to identify the most critical barriers in determining health outcomes in Black youth and White youth. Methods: This observational study included a sample of youth aged 2–17 years with epilepsy obtained by combining data from four different studies. A total of 226 caregivers and 43 adolescents reported on adherence barriers. An electronic monitor was used to measure adherence to the primary antiepileptic drug. Racial disparities in individual barriers were examined. The relative importance of different types of barriers in determining clinical outcomes was evaluated in both Black and White youth. Results: Adherence barriers, including running out of medications, access to pharmacies, competing demands, and difficulty swallowing, disproportionally affected Black children with epilepsy compared to White children. System- and community-level barriers emerged as the most important in determining seizure outcomes among Black youth. Both system- and individual-level barriers, on the other hand, were important for adherence outcomes. Conclusions: System- and community-level barriers, as opposed to individual-level barriers, are more highly endorsed by Black families compared to White families. These barriers are also the most critical in driving seizure outcomes among Black youth. There is a critical need to shift from a primary focus on individual-level barriers to an approach that deliberately targets larger systemic barriers to reduce the existing adherence and health disparities that affect Black children with pediatric conditions.